Cyclic-di-GMP and oprF Are Involved in the Response of Pseudomonas aeruginosa to Substrate Material Stiffness during Attachment on Polydimethylsiloxane (PDMS) - Song, Fangchao; Wang, Hao; Sauer, Karin; Ren, Dacheng (Frontiers in Microbiology, 2018)
Recently, we reported that the stiffness of poly(dimethylsiloxane) (PDMS) affects the attachment of Pseudomonas aeruginosa, and the morphology and antibiotic susceptibility of attached cells. To further understand how P. aeruginosa responses to material stiffness during attachment, the wild-type P. aeruginosa PAO1 and several isogenic mutants were characterized for their attachment on soft and stiff PDMS. Compared to the wild-type strain, mutation of the oprF gene abolished the differences in attachment, growth, and size of attached cells between soft and stiff PDMS surfaces. These defects were rescued by genetic complementation of oprF. We also found that the wild-type P. aeruginosa PAO1 cells attached on soft (40:1) PDMS have higher level of intracellular cyclic dimeric guanosine monophosphate (c-di-GMP), a key regulator of biofilm formation, compared to those on stiff (5:1) PDMS surfaces. Consistently, the mutants of fleQ and wspF, which have similar high-level c-di-GMP as the oprF mutant, exhibited defects in response to PDMS stiffness during attachment. Collectively, the results from this study suggest that P. aeruginosa can sense the stiffness of substrate material during attachment and respond to such mechanical cues by adjusting c-di-GMP level and thus the following biofilm formation. Further understanding of the related genes and pathways will provide new insights into bacterial mechanosensing and help develop better antifouling materials.